Geographic Information System (GIS)-Based Road Damage Mapping in Google Earth for Village Infrastructure Planning - Novia Ratnasari; Anisa Hudi Widaningrum; Anggraeni Hadi Pratiwi (G-Tech: Jurnal Teknologi Terapan, 2025)
The quality of village infrastructure plays a vital role in improving community welfare through economic growth. Tuban Regency, with its diverse geographical features such as coastal areas and limestone hills, frequently experiences road damage that hinders accessibility and development. To address this issue, the local government promotes sustainable development strategies, particularly through road infrastructure improvements funded by the Village Fund Allocation (ADD) program. However, feasibility studies on road damage in Sumurjalak Village remain inefficient in terms of time and cost, and lack accuracy due to the absence of supporting digital data. This study proposes a novel approach by integrating Geographic Information Systems (GIS) with Google Earth technology to map and assess road damage. Unlike conventional manual surveys or paper-based documentation, this integration provides a more efficient, accurate, and visually interactive method of spatial analysis. Using the Action Research method, which consists of five stages problem identification, data collection, planning, implementation, and evaluation this study demonstrates that GIS-based mapping significantly enhances the efficiency and accuracy of infrastructure assessments. The resulting digital documentation can serve as a decision-support tool for stakeholders and offer a scalable and replicable model for rural infrastructure planning, representing a significant advancement over previous approaches.